2019
DOI: 10.1038/s41467-019-11123-x
|View full text |Cite
|
Sign up to set email alerts
|

Live cell imaging reveals 3′-UTR dependent mRNA sorting to synapses

Abstract: mRNA transport restricts translation to specific subcellular locations, which is the basis for many cellular functions. However, the precise process of mRNA sorting to synapses in neurons remains elusive. Here we use Rgs4 mRNA to investigate 3′-UTR-dependent transport by MS2 live-cell imaging. The majority of observed RNA granules display 3′-UTR independent bidirectional transport in dendrites. Importantly, the Rgs4 3′-UTR causes an anterograde transport bias, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 61 publications
2
55
0
Order By: Relevance
“…The mechanisms underlying the initial capture and enduring sequestration of mRNAs are not well understood. Recent work with Rgs4 indicated that neuronal activity is essential for the capture of mRNAs at dendritic spines; inhibition of neuronal activity with TTX suppressed mRNA-spine association ( 24 ). An activity dependence for spine capture has also been reported with β-actin during glutamate uncaging ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms underlying the initial capture and enduring sequestration of mRNAs are not well understood. Recent work with Rgs4 indicated that neuronal activity is essential for the capture of mRNAs at dendritic spines; inhibition of neuronal activity with TTX suppressed mRNA-spine association ( 24 ). An activity dependence for spine capture has also been reported with β-actin during glutamate uncaging ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…mRNAs are believed to be transported in a translationally quiescent state, likely only engaged in translation near synapses ( 22 , 23 ). The dynamic and bidirectional ( 22 , 24 26 ) scanning behavior of mRNAs in dendrites allows, in principle, for the capture and translation of mRNAs as needed for proteome maintenance and remodeling ( 22 , 23 ). Our understanding of these processes, however, is largely derived from live imaging experiments for a limited number of individual candidate mRNAs including β-actin ( 22 , 25 ) and Arc ( 27 ); the relationship between the sequestration/capture of RNAs and their translation during plasticity is not well understood.…”
mentioning
confidence: 99%
“…mRNAs are believed to be transported in a translationally quiescent state-likely only engaged in translation near synapses 22,23 . The dynamic and bidirectional 22,2426 scanning behavior of mRNAs in dendrites allows, in principle, for the capture and translation of mRNAs as needed for proteome maintenance and remodeling 22,23 . Our understanding of these processes, however, is largely derived from live imaging experiments for a limited number of individual candidate mRNAs Beta actin 22,25 and Arc 27 ; the relationship between the sequestration/capture of RNAs and their translation during plasticity is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…mRNA exhibited a complex migratory behavior with an anterograde bias, mediated by the RNA-binding protein Staufen 2. [48] Moreover,…”
Section: F I G U R Ementioning
confidence: 99%
“…By means of the MS2‐MCP system in rat hippocampal neurons, it was shown that a reporter mRNA containing the 3′UTR from Rgs4 mRNA exhibited a complex migratory behavior with an anterograde bias, mediated by the RNA‐binding protein Staufen 2. [ 48 ] Moreover, Rgs4 3′UTR also increased mRNA docking and undocking events closer to synapses. However, the anterograde transport bias was not only dependent on the 3′UTR but also on neuronal activity, since its inhibition abolished the bias.…”
Section: Pre‐translational Mrnp Transportmentioning
confidence: 99%